Learning Effectiveness Using Picture and Picture Model to Improve Understanding of The Concept Substance And Change for Class VII Students of SMP - Asrinaldi (Journal of Indonesian Science Teachers, 2025)
The low understanding of the concept of physics science of grade VII junior high school students due to the limited application of innovative learning models, so the purpose of this research was to analyze the effectiveness of the Picture and Picture learning model in improving students' conceptual understanding of the material of substances and changes at SMPN 20 Pekanbaru. The research method used a quasi-experimental design with a Posttest-Only Control Group Design. The research sample consisted of two classes, namely the experimental class that applied the Picture and Picture learning model and the control class that used conventional learning methods. Data were collected through a conceptual understanding test given after the learning took place. Data analysis was carried out descriptively and inferentially. The results of the descriptive analysis showed that the experimental class obtained a conceptual understanding score in a good category, while the control class was in a fairly good category. Hypothesis testing using the Mann-Whitney test showed a significant difference between students' conceptual understanding in the experimental class and the control class. It can be concluded that the Picture and Picture learning model is effective in improving students' conceptual understanding of the material of substances and changes. This model is suitable for use as an alternative innovative learning to improve the quality of learning in junior high schools.